Interaction of oxidized copper surfaces with alkanethiols in organic and aqueous solvents. the mechanism of Cu2O reduction - Calderon, Cecilia Andrea (2010)
The interaction of 1-octanethiol, 1,8-octanedithiol, 1-hexadecanethiol, and 16-mercaptohexadecanoic acid with polycrystalline copper surfaces was investigated comparatively using forming solutions with polar (0.05 M NaOH solution) and apolar (n-hexane) solvents. The thiol layers were formed on the freshly chemically polished copper surface as well as on the anodically oxidized surface. The effects of the alkanethiol chain length and terminal group on the blocking properties of the surface were investigated. We show for the first time that compact monolayers and multilayers can be obtained from an alkaline forming solution. Copper oxides are completely reduced in the alkaline forming solution for all of the thiols investigated after an immersion time of 45 min. On the contrary, the presence of a surface oxide was always detected after the formation of the thiol layer in the n-hexane solution. The mechanism of Cu 2O reduction by thiols was investigated by means of density functional theory calculations. The surface reactions involve the protonation of the surface oxygen atoms of the oxide which act as Lewis base sites. In the alkaline electrolyte, the proton transfer involves the water molecules of the solvent, whereas in the n-hexane solution the proton transfer involves the -SH group of the alkanethiol. The surface reactions are not the rate limiting step because they have very low activation energy barriers. The higher reduction rate observed in the alkaline thiol solutions is due to the high concentration of the reacting water molecules, whereas the lower reaction rate in the n-hexane solutions correlates with the lower concentration of the reactant alkanethiol molecules.